Simplified seismic resistant design of base isolated single pylon cable-stayed bridge - Han, Q.; Wen, J.; Du, X.; Zhong, Z.; Hao, Hong (Springer, 2018)
© 2018 Springer Science+Business Media B.V., part of Springer Nature The seismic vulnerability of single pylon cable-stayed bridges under strong ground motions in the transverse direction is of great concern to earthquake engineering researchers and bridge engineers. Introduction of base isolation to cable-stayed bridges has been proved very effective in reducing seismic forces in the bridges in previous studies. This paper proposes a direct displacement based seismic design (DDBD) procedure for base isolated cable-stayed bridge under transverse seismic excitation. One of the key aspects of the DDBD is the realization of a uniform transverse target displacement of the deck under seismic excitation, which is achieved by appropriate design of the isolator stiffness at the bottom of the pylon and the ends of the deck. The proposed DDBD procedure is applied in this paper to the seismic design of a single pylon cable-stayed bridge isolated by friction pendulum bearings. The effectiveness and the accuracy of the resulting design are checked by nonlinear time history analyses. The numerical results indicate that the proposed DDBD procedure can predict the deck displacement profile and amplitudes, as well as the base shear within a reasonable degree of accuracy. The case study demonstrates that the proposed DDBD procedure is sufficiently accurate and practical for the seismic design of base isolated single pylon cable-stayed bridges.